2008
DOI: 10.1021/ja800230k
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalently Connected Micelles, Nanoparticles, and Metal-Functionalized Nanocages Using Supramolecular Self-Assembly

Abstract: An SCS "pincer"-based nitroxide-mediated polymerization (NMP) initiator has been synthesized and utilized to polymerize tert-butyl acrylate ( ( t )BuA), affording polymers with control over molecular weight and polydispersity. (1)H NMR spectroscopy indicates that the sulfur end group remains intact after deprotection of the P ( t )BuA segment to yield a poly(acrylic acid) segment. The hydrophilic polymer-tethered SCS ligand has been demonstrated to bind to palladium(II), as characterized by a distinctive Pd-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 92 publications
1
127
0
Order By: Relevance
“…Solutions of P(MOx) nb-P(t-BA) m (0.3 mg.mL -1 ) were prepared in DMF which was a good solvent for both P(MOx) and P(t-BA) blocks, dialyzed against MilliQ water, and finally filtered through a membrane with a nominal pore size of 0.45 μm. 1,45 Thus, in water, we expected copolymers to form micelles composed of P(t-BA) micellar core surrounded by a P(MOx) corona. The morphology of polymer aggregates was first studied by atomic force microscopy (AFM) and transmission electron microscopy (TEM).…”
Section: Self-assembling Of P(mox) N -B-p(t-ba) M Amphiphilic Copolymersmentioning
confidence: 99%
“…Solutions of P(MOx) nb-P(t-BA) m (0.3 mg.mL -1 ) were prepared in DMF which was a good solvent for both P(MOx) and P(t-BA) blocks, dialyzed against MilliQ water, and finally filtered through a membrane with a nominal pore size of 0.45 μm. 1,45 Thus, in water, we expected copolymers to form micelles composed of P(t-BA) micellar core surrounded by a P(MOx) corona. The morphology of polymer aggregates was first studied by atomic force microscopy (AFM) and transmission electron microscopy (TEM).…”
Section: Self-assembling Of P(mox) N -B-p(t-ba) M Amphiphilic Copolymersmentioning
confidence: 99%
“…In addition, the absence of free arm-micelle equilibrium reduces the degree of catalyst leaching. Unimolecular polymeric nanoreactors have been obtained by cross-linking linear polymers, after self-assembly in micellar form, at the level of either the outer shell [3][4][5][6], the inner core [7][8][9][10] or an intermediate corona [11,12]. Nanoreactors with a nanogel core have also been obtained by direct functionalization and cross-linking starting from linear polymers as macroinitiators [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Theoretical work has shown that the domain size and morphology of the phase-separated structures critically depend on the strength of the interpolymer noncovalent interactions. [5][6][7][8][9][10] To achieve these attractive enthalpic interpolymer interactions, end-functionalized homopolymers have been prepared with functional groups capable of noncovalent assembly such as hydrogen bonding, [11][12][13][14][15][16][17][18][19][20] ionic, 21 transition-metal, 22,23 host-guest, [24][25][26] and fluorophilic 27 interactions. Typically, these functional groups are attached to a homopolymer via a short, aliphatic spacer.…”
Section: Introductionmentioning
confidence: 99%